Monascus red dye as alternative colorant for salted duck eggs - Santiago, Ma. Erlyne S.
The study aimed to determine the suitability of Monascus red as an alternative colorant for salted eggs by assessing its solubility in water and its stability in aqueous solutions (20 mg/ml) under different pH levels (4, 7 and 8), storage temperatures (15°C, 25°C and 55°C), processing temperatures (85°C and 100°C) and storage period (0, 3 and 5 days). The resulting Monascus-colored salted eggs were also evaluated for sensorial properties and color fastness, and compared to Basic Fuchsin-colored salted eggs in terms of color attributes and cost. Results showed that Monascus red solutions exhibited high solubility in water (90.9 g/L at 25°C), and stability towards neutral and alkaline pH, and low temperature. However, Monascus red solution at acidic pH showed less drastic change in a one-week storage period at room temperature.Low pH and high temperature resulted in higher L, a and b values which corresponded to an orange-red hue. The resulting color did not meet the purplish-pink hue of Basic Fuchsin. However, the mordanting properties of acid and high temperature, resulted in greater color impartation and a lightness value close to that imparted by Basic Fuchsin. Overall, Basic Fuchsin showed wider color range, and lower cost due to smaller mass concentration used compared to Monascus red.Monascus still presented to be a promising alternative colorant for salted eggs due to its safety, storage stability and high solubility. Studies on the marketability of Monascus-colored salted eggs are recommended.